The Crescent on the Temple The Dome of the Rock as Image of the Ancient Jewish Sanctuary. - Berger, Pamela (Leiden : BRILL, 2012)
"The Crescent on the Temple" elucidates how the Dome of the Rock came to stand for the Temple of Solomon in Christian, Muslim, and Jewish art. That "Temple," represented as the Muslim shrine, is often surmounted by a crescent.
Chapter Fourteen The Dome of the Rock as the Temple: Nineteenth Century Itinerary SheetsChapter Fifteen The Dome of the Rock as the Temple in Cloth and Yarn; Chapter Sixteen The Dome of the Rock as Protective Image; Chapter Seventeen The Waning of the Dome of the Rock as the Image of the Temple; Chapter Eighteen The Dome of the Rock and the Temple in Our Time; Works Cited; Appendix; Index
Description based upon print version of record.
Keywords: Jewish art and symbolism -- Themes, motives; Qubbat al-S?akhrah (Mosque : Jerusalem) -- In art; Temple of Jerusalem (Jerusalem) -- In art; Fine Arts; Religion; Qubbat al-Ṣakhrah (Mosque : Jerusalem) -- In art; Temple of Jerusalem (Jerusalem) -- In art; Jewish art and symbolism -- Themes, motives; RELIGION / Judaism / Rituals & Practice; Electronic books